Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/09544062211057045
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on the muzzle response characteristics of small unmanned ground vehicles with small arms

Abstract: The muzzle response is the main feature affecting the firing accuracy of weapons. To research the muzzle response characteristics of small unmanned ground vehicles with small arms (SUGVsSA) during shooting, this paper designs a test method that combines an inertial measurement system (IMS) with a high-speed photogrammetric system (HSPS) to measure the muzzle response. That is, an inertial measurement unit (IMU) is fixed onto the gun body to record the three-dimensional angular motion of the barrel; meanwhile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The R 2 score was used as the evaluation citation of the model of bullet prediction for impact points, as shown in equation (2). The R 2 score of the bullet landing prediction model is shown in Table 1, and the R 2 values of the numerical predictions of the horizontal and vertical offsets of the bullet landing are both greater than 0.9, which showed that the model of bullet prediction for impact points is accurate for the prediction for impact points.…”
Section: Fig4 Network Structure Diagram Of Prediction For Impact Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The R 2 score was used as the evaluation citation of the model of bullet prediction for impact points, as shown in equation (2). The R 2 score of the bullet landing prediction model is shown in Table 1, and the R 2 values of the numerical predictions of the horizontal and vertical offsets of the bullet landing are both greater than 0.9, which showed that the model of bullet prediction for impact points is accurate for the prediction for impact points.…”
Section: Fig4 Network Structure Diagram Of Prediction For Impact Pointsmentioning
confidence: 99%
“…Small-caliber unmanned intelligent weapons (SCUIW) are autonomous fire strike systems that combine traditional weapons, optoelectronic sights, and servo control modules [1][2][3]. Firing accuracy is the most important performance index of small-caliber unmanned intelligent weapons, and the main influence factors are hit probability estimation accuracy, image servo tracking accuracy, and firing timing [4][5][6].…”
Section: Introductionmentioning
confidence: 99%